Macroinvertebrados bentónicos y ensayos toxicológicos para evaluar la calidad del agua y del sedimento del río Rímac, Lima, Perú - Pascual, Gissela (2020)
The aim of this research was to use the benthic macroinvertebrates (MIB) and toxicological assessment tests to evaluate the water and sediment quality of the Rimac river (Lima-Peru) in wet and dry seasons in 2009. Twelve sampling stations (E1 to E12) were established, considering the sources of contamination. At each station, physical and chemical data, MIB, and water and sediment toxicity with Daphnia magna and Chironomus calligraphus were measured. The wet season had higher pH; however, higher values ​​of specific conductivity, total solids, dissolved oxygen and transparency were observed in the dry season. Differences in the abundance of Planorbidae, Baetidae, Chironomidae, Tipulidae and Empididae were observed between wet and dry seasons. The diversity and evenness index were higher in wet season, but the dominance and abundance index were higher in the dry season. The dendrogram of similarity based on the MIB showed three groups which would be related to the activities carried out in the basin at the time of flood: the first group responding to mining liabilities, the second group responding to domestic agriculture, and a third group responding to agriculture, industry and domestic impact. Water quality was estimated using the biotic index, EPT (Ephemeroptera – Plecoptera – Trichoptera) (mostly bad about 75%) and ABI (Andean Biotic Index) (poor - bad: 16.67-33.33%). For toxicological tests with D. magna and C. calligraphus only sampling station E1 was toxic at the time of flood.